EVALUATION OF ANTIDIARRHOEAL POTENTIAL OF METHANOLIC ROOT EXTRACT OF Cassia sieberiana DC (Fabaceae) IN MICE - Mohammed, Z; Bello, H; Yaro, A.H; A. Ahmed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Cassia sieberiana (Fabaceae) is a tropical plant that has been reported to be traditionally used in Nigeria for the treatment of general body pain, ulcer, dysmenorrheal and diarrhoea. The phytochemical screening, toxicity evaluation and antidiarrhoeal activity studies of the methanolic extract of C. sieberiana were carried out. The anti-diarrhoeal activity was evaluated in mice using the experimental models of castor oil-induced diarrhoea, gastrointestinal motility test and castor oil-induced enteropooling in mice. A standard anti-diarrhoeal agent, loperamide, was used as reference drug. Phytochemically, the extract revealed the presence of flavonoids, terpenoids, tannins, saponins, glycosides and anthraquinones. The extract did not cause death nor show any sign of acute toxicity in the mice at the tested doses, thus implying that it was well tolerated by the mice. The different doses (100, 200 and 400 mg/kg) of the extract showed dose dependent and significant (p<0.05) decrease in the number of wet feaces in the castor oil-induced diarrhoea , inhibition of the propulsive activity of charcoal meal through the gastrointestinal lumen and reduction of intra-luminal accumulation in the castor oil induced enteropooling in mice. The antidiarrhoeal activity was comparable to that of loperamide at the higher dose of 400 mg/kg. It could be concluded from the results that C. sieberiana possess potent anti-diarrhoeal activity which validates its use as an antidiarrhoeal agent in traditional medicine practice.